The verbal system of the Aramaic of Daniel : an explanation in the context of grammaticalization - Li, Tarsee. (Studies in the Aramaic Interpretation of Scripture, 2009)
This book explains the verbal system of the Aramaic of Daniel in the context of current research on grammaticalization, which, though first mentioned by Meillet in 1912, did not flourish until the beginning of the 1980's, and has only more recently been applied to the study of Ancient Near Eastern languages. Although various aspects of the Aramaic of Daniel have been subject of numerous studies, including a few exhaustive studies on the verbal system in the last century, it remains among the most difficult to explain. The explanation offered here is coherent with the historical development of Aramaic as well as the observable tendencies in the development of human languages in general.